ANALYSIS OF STRUCTURAL CHANGES IN THE REGIONAL INDUSTRY STRUCTURE AND DYNAMICS OF ECONOMIC GROWTH (Marketing Journal, 2025)
This article provides a theoretical and empirical analysis of structural changes in the regional industrial structure and their impact on the dynamics of economic growth. The study examines changes in the sectoral shares of industry, the level of № 1 645 diversification, and structural shifts in relation to economic growth rates. Based on the structural shift index, concentration coefficient, and time -series analysis, the effectiveness of transformational processes occurring in the regional economy is assessed. The results indicate that a shift in the industrial structure toward high value - added and technologically advanced sectors ensures greater stability of economic growth. Furthermore, the optimization of the industrial structure is substantiated as a priority direction of regional economic policy.
Keywords: regional economy; industrial structure; structural change; economic growth dynamics; diversification; industrial policy; concentration index; structural shift; value added; competitiveness; innovative development; sectoral efficiency